2003
DOI: 10.1002/ajmg.a.20022
|View full text |Cite
|
Sign up to set email alerts
|

Lambert–Eaton Myasthenic syndrome in a child with an autoimmune phenotype

Abstract: We report on a child with a family history of autoimmune defects, who presented at the age of 3(1/2) years with alopecia and Graves disease. He subsequently developed vitiligo and psoriasis. At 9(1/2) years, he developed an autoimmune form of Lambert-Eaton Myasthenic syndrome (LEMS) with a significant elevation of glutamic acid decarboxylase (GAD) autoantibodies. Shortly thereafter he developed chronic urticaria. HLA associations were present for Graves disease, vitiligo, psoriasis, and IgA deficiency. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
1
10
0
2
Order By: Relevance
“…An association between GD and IgAD was previously suggested in various case reports (32)(33)(34)(35), and a small screening study showed that IgAD is overrepresented among GD patients (36) (Table 1), although this could not be confirmed by other groups (37)(38)(39).…”
Section: Igad and Graves Diseasementioning
confidence: 79%
“…An association between GD and IgAD was previously suggested in various case reports (32)(33)(34)(35), and a small screening study showed that IgAD is overrepresented among GD patients (36) (Table 1), although this could not be confirmed by other groups (37)(38)(39).…”
Section: Igad and Graves Diseasementioning
confidence: 79%
“…LEMS is even rarer in children, and only 11 pediatric cases have been reported in the literature (table). [2][3][4][5][6][7][8][9][10] Neoplasm was associated with 4 of these cases. 4,6 We present the case of a 3-year-old boy with LEMS, supported by the clinical presentation, characteristic findings on EMG, and elevated serum P/Q-type voltage-gated calcium channel antibodies.…”
mentioning
confidence: 99%
“…Of the 11 cases reported, however, 4 of these had positive voltage-gated calcium channel antibodies. 2,5,7 Thus, the value of testing for P/Q-type voltage-gated calcium channel antibodies in children with suspected LEMS is unclear but may be helpful in circumstances where the diagnosis is unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Autoimmune polyglandular syndromes (APS) are a group of rare disorders defined by autoimmune activity against endocrine and nonendocrine organs. APS type IIIC includes autoimmune thyroiditis (AIT), vitiligo and/or alopecia, and/or other autoimmune disease such as chronic spontaneous urticaria (CSU) . CSU is a mast cell‐driven disease characterized by recurrent wheals and/or angioedema lasting for at least 6 weeks .…”
Section: Characteristic Features Of Autoimmune Polyglandular Syndromementioning
confidence: 99%